2012
DOI: 10.1148/radiol.12111869
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy after CT Diagnosis of Diverticulitis to Exclude Colon Cancer: A Systematic Literature Review

Abstract: Purpose:To estimate the prevalence of underlying adenocarcinoma of the colon in patients in whom acute diverticulitis was diagnosed at computed tomography (CT) and to compare that to the prevalence of colon cancer in the general population. Materials and Methods:A comprehensive literature review was performed to find articles in which patients with CT diagnosis of acute diverticulitis underwent surgery, colonoscopy, or barium enema study within 24 weeks. Patients meeting these criteria were included for analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 61 publications
4
47
0
2
Order By: Relevance
“…[18][19][20][21] In these studies, the prevalence of CRC among patients with radiologically diagnosed diverticulitis ranged from 1.0% to 2.1%. However, 3 of these studies excluded patients with complicated diverticulitis and patients who underwent surgical management for their diverticular disease.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[18][19][20][21] In these studies, the prevalence of CRC among patients with radiologically diagnosed diverticulitis ranged from 1.0% to 2.1%. However, 3 of these studies excluded patients with complicated diverticulitis and patients who underwent surgical management for their diverticular disease.…”
Section: Discussionmentioning
confidence: 98%
“…However, 3 of these studies excluded patients with complicated diverticulitis and patients who underwent surgical management for their diverticular disease. [18][19][20] The exclusion of patients with complicated diverticulitis may introduce selection bias, as the prevalence of CRC was determined only in patients with uncomplicated cases who underwent follow-up colonoscopy. The prevalence of CRC was found to be higher in patients with complicated diverticulitis diagnosed radiologically, leading some authors to conclude that only complicated diverticulitis requires follow-up colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…However, this advice is based only on expert opinion [11,12]. Recently, results have been published from retrospective studies [13][14][15][16] and one systematic review [17], showing a comparable yield from colonoscopy or other imaging studies after an episode of diverticulitis. In these studies malignant tumours were found in 0-2.8% of patients who underwent colonic imaging [13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic literature search on the benefit of colonoscopy from the perspective of the detection of colon carcinomas up to 24 weeks after CT diagnosis of diverticulitis identified 10 studies with 771 documented patients [65]. In these, the rate of colorectal carcinomas was 2.1% (95% CI 1.2-3.2) and thus markedly above the expected prevalence (0.68%) in the US population aged >55 years.…”
Section: History-taking Basic Diagnostic Procedures Differential DImentioning
confidence: 99%